Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.3748/wjg.v13.i30.4080
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C Virus non-structural 5A abrogates signal transducer and activator of transcription-1 nucleartranslocation induced by IFN-α through dephosphorylation

Abstract: AIM:To study the effect of Hepatitis C virus nonstructural 5A (HCV NS5A) on IFNα induced signal transducer and activator of transcription-1 (STAT1) phosphorylation and nuclear translocation. METHODS:Expression of STAT1 Tyr701 phosphorylation at different time points was confirmed by Western blot, and the time point when p-STAT1 expressed most, was taken as the IFN induction time for further studies. Immunocytochemistry was used to confirm the successful transient transfection of NS5A expression plasmid. Immuno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 27 publications
(13 reference statements)
0
10
0
Order By: Relevance
“…In our study, substitutions N248H and E269K found in the "medium" lineage at p45 and S272P in the "low" lineage (mixed at p45 and dominant by p100) are located within the ISDR. Studies on the mechanisms by which NS5A counteracts IFN-␣ activity have not given conclusive results (91,(93)(94)(95)112).…”
Section: Discussionmentioning
confidence: 99%
“…In our study, substitutions N248H and E269K found in the "medium" lineage at p45 and S272P in the "low" lineage (mixed at p45 and dominant by p100) are located within the ISDR. Studies on the mechanisms by which NS5A counteracts IFN-␣ activity have not given conclusive results (91,(93)(94)(95)112).…”
Section: Discussionmentioning
confidence: 99%
“…27 The sequence of a certain NS5A region, called the interferon sensitivity-determining region, 28 is highly associated with the final outcome of IFNa therapy. Furthermore, experimental evidence suggests that the function of NS5A includes abrogation of STAT-1 translocation, 29 suppression of STAT-1 phosphorylation 30 and repression of the protein kinase R protein kinase. [31][32][33] Because of its important function in controlling HCV replication, many molecules have been designed to target NS5A, some of which have exhibited promising treatment outcomes in clinical research.…”
Section: Ifn-a-induced Trim22 Interrupts Hcv Replicationmentioning
confidence: 99%
“…HCV core prevents phosphorylation of STAT1 in response to IFN-α [17] and NS5A prevents translocation of pSTAT1 to the nucleus [18]. Shorter telomeres are associated with defective activation of STAT5 in mouse macrophages [19].…”
Section: Introductionmentioning
confidence: 99%